Linguistic Creativity and Translanguaging in Trilingual (Indonesian-English-Javanese) Posts on Vincanyoo’s Instagram - Hagung Yudistira Utomo; Setiono Sugiharto; Engliana (Masyarakat Linguistik Indonesia, 2026)
This study investigates translanguaging practices and linguistic creativity in trilingual Indonesian–English–Javanese Instagram videos by Vincanyoo, an Indonesian influencer. It aims to examine how translanguaging is manifested through verbal and multimodal resources and how these practices construct humor, linguistic creativity, and digital identity. Using a qualitative multimodal discourse analysis, this study analyzes seven Instagram videos uploaded in 2025, supported by an interview with the content creator. The data include spoken utterances, captions, hashtags, gestures, gaze, facial expressions, costumes, props, settings, and interview responses. ELAN-assisted transcription was used to organize the data into time-based analytical tiers, enabling the researcher to connect verbal language with embodied and visual resources. The findings show that Vincanyoo’s translanguaging practices are realized through Indonesian–English translanguaging, Indonesian–Javanese translanguaging, persona-based translanguaging, lexical borrowing, cultural translanguaging, prosodic exaggeration, and multimodal translanguaging. Indonesian functions as an accessibility bridge for wider audiences, English indexes coolness, modernity, and global identity, while Javanese indexes local intimacy, emotional intensity, domestic authority, and humor. The study also reveals that humor and creativity are constructed through contrasting personas such as Ibu Barat ‘Western Mom’, Ibu Jawa ‘Javanese Mom’, Istri Barat ‘Western Wife’, and Istri Jawa ‘Javanese Wife’, supported by gestures, costumes, props, and digital framing. This study contributes to translanguaging and digital sociolinguistic research by showing that regional languages such as Javanese can function as central resources for humor, identity construction, and multimodal creativity in Indonesian social media discourse.